STRATEGI GURU DALAM MENGATASI KESULITAN MEMBACA SISWA KELAS V DI SD NEGERI 15 TAMPE - Ratna Ratna; Felisitas Viktoria Melati (STKIP Subang, 2026)
This study aims to describe the phonics strategy implemented by teachers in overcoming reading difficulties among fifth-grade students at SD Negeri 15 Tampe and to identify the supporting and inhibiting factors in its implementation. This research used a qualitative descriptive approach. The subjects of the study were the fifth-grade teacher and fifth-grade students at SD Negeri 15 Tampe. Data were collected through observation, interviews, and documentation. The data analysis techniques included data reduction, data presentation, and drawing conclusions. The results showed that the phonics strategy was implemented through activities such as recognizing letters and sounds, combining letters into syllables, reading words gradually, reading aloud, and providing individual guidance to students experiencing reading difficulties. The strategy helped improve students’ ability to recognize letters, reading fluency, and pronunciation accuracy. Supporting factors included teacher commitment, the use of learning media such as letter cards, and support from the school environment. Meanwhile, inhibiting factors included limited learning time, differences in students’ reading abilities, and students’ lack of self-confidence. Therefore, the phonics strategy can be considered effective in helping students overcome reading difficulties, especially in mastering letter-sound relationships and improving reading fluency